參考
實踐
高級版
登錄
繁體中文
English
Español
日本語
简体中文
繁體中文 ✔
6
x
−
9
=
5
x
+
4
6x-9=5x+4
6
x
−
9
=
5
x
+
4
+
−
.
ln
>
<
×
÷
/
log
≥
≤
(
)
log
x
=
%
選擇主題
例子
"(x+1)/2+4=7"
"factor x^2+5x+6"
"integrate cos(x)^3"
更多 »
6x-9=5x+4
6x-9=5x+4
6x-9=5x+4
1
向兩邊添加
9
9
9
。
6
x
=
5
x
+
4
+
9
6x=5x+4+9
6
x
=
5
x
+
4
+
9
2
簡化
5
x
+
4
+
9
5x+4+9
5
x
+
4
+
9
至
5
x
+
13
5x+13
5
x
+
1
3
。
6
x
=
5
x
+
13
6x=5x+13
6
x
=
5
x
+
1
3
3
從兩邊減去
5
x
5x
5
x
。
6
x
−
5
x
=
13
6x-5x=13
6
x
−
5
x
=
1
3
4
簡化
6
x
−
5
x
6x-5x
6
x
−
5
x
至
x
x
x
。
x
=
13
x=13
x
=
1
3
完成
檢查答案 ▼
x=13
喜歡這個答案?分享它!
Copy Link
我們如何才能使這答案幫到您更多?